Image processing methods integrated to imaging and material characterisation for the study of incunabula illustrations: an innovative multi-analytical approach on a case-study - Bottura-Scardina, S. (2020)
This study focuses on the application of a multi-analytical approach combining image processing techniques, imaging studies and material characterisation of a French late fifteen-early sixteen century incunabulum – the BPE, Inc.438. The first study goal was to verify the potential of computational methods in NIR imaging to retrieve accurate reconstructions of the engraving printings by Germain Hardouyn. For this aspect, two representative scenes were chosen: Trinity, f.8r; Saint Anthony the Abbot, f.61v. The applied methodology allowed faster creation of digital reconstructions while the material analysis proved the use of azurite, malachite, vermilion, lead white and ochres, and their NIR response was assessed in the context of the digital processing. The second goal was to make a comparison between chosen illuminations and engraved references of the same representations from two incunabula of the British Library, unravelling the illuminator’s intentional iconographic alteration based on visual and theological criteria.